(untitled) (Journal of Contemporary Philology, 2022)
This paper aims to explore the translatability of the drag terminology used in the popular reality competition RuPaul’s Drag Race (RPDR), from English into Macedonian. There are two hypotheses on which the study is based: 1) The people who use drag terms find it more natural to use them as borrowings (i.e. in their original form (in English)) and 2) If the drag terms were to be taken into Macedonian, they would more often be taken as adapted borrowings (i.e. undergo naturalisation), rather than be translated with a Macedonian equivalent. Two research methods were employed. The first was the analysis of Macedonian articles with drag-related content, as well as parts from the translation of How To Be Gay by David M. Halperin (trans. Ognen Chemerski), in order to discover preexisting translations. The second included a survey aiming to explore whether translation of the terminology is possible, and to gather translations. Upon analyzing the findings, it is evident that English forms heavily influence how Macedonian speakers use these terms and how they would translate them. However, complete translation is not entirely impossible, so long as it strives to retain both the meaning and the form, and to utilize creativity and word-play.